Early Maladaptive Schemas’ Associations with Big-Five Personality Traits in Two Non-Clinical Adult Samples from Different Cultural Backgrounds (European Journal of Mental Health, 2024)
Introduction: While personality traits and early maladaptive schemas (EMSs) can affect an individual’s behavior and well-being, the links between these constructs are under-researched, especially in non-clinical samples.Aims: Two studies were conducted to address these links, intending to explore their specifics, as previous research evidenced various associations’ models.Methods: In Study 1, the sample consisted of 120 respondents (65.0% females) living in the UK and the USA. In Study 2, the sample consisted of 244 respondents (68.0% females) living in Lithuania. In both studies, most of the respondents were aged 18-25. The survey was administered online. Studies 1 and 2 applied the Big Five Inventory and Young Schema Questionnaire.Results: In Study 1, neuroticism was significantly positively associated with 17 EMSs. Extraversion stood significantly negatively related to 12 EMSs, conscientiousness was significantly negatively related to 15 EMSs, openmindedness stood significantly negatively related to 2 EMSs, but significantly positively related to admiration, and agreeableness appeared significantly negatively related to 9 EMSs. In Study 2, neuroticism was significantly positively associated with 16 EMSs. Extraversion stood significantly negatively related to 9 EMSs, conscientiousness was significantly negatively related to 12 EMSs, open-mindedness and agreeableness were significantly negatively related to 10 EMSs.Conclusions: Study 2 partly failed to replicate the results of Study 1, which implies that the model of links between EMSs and personality traits could be impacted by cultural factors, and needs further investigation.